Development of basic requirements for an automated heat treatment site of a ring‑rolling complex - V. E. Antonyuk; S. G. Sandomirski; S. O. Nikiforovich; V. V. Rudyi; N. P. Timoshenko (Литьë и металлургия, 2022)
Thermal furnaces and auxiliary equipment for the main thermal treatments (normalization, annealing, isothermal annealing, improvement) are considered, to which products must be subjected after ring rolling to create mechanical properties and structures in annular workpieces that improve the machinability by cutting. The basic requirements for thermal furnaces optimal for an automated section of heat treatment of annular blanks after ring rolling have been developed. It is shown that to perform all the specified types of heat treatment, it is advisable to use the same type of thermal equipment that has the same overhaul life and service life. This makes it possible to stop the automated line at the same time and simultaneously provide service for all components of the line. The use of shaft furnaces for heat treatment in an automated heat treatment line is not appropriate, since there is practically no experience of embedding them in such lines.